IMPROVING THE EFFECTIVENESS OF MANAGEMENT DECISIONS IN THE PROCESS OF ECONOMIC AND SOCIAL POLICY-MAKING BASED ON ECONOMIC AND MATHEMATICAL MODELING - Ventsel , Viktor (Theory and Practice of Public Administration, 2020)
The topical problem is the adoption of state agencies effective and reasonable management decisions that need to achieve the goals of economic and social policy within available financial resources. Among the management tools that can assists to improving the quality of managerial decisions in the economic and social spheres is economic and mathematical modeling, which is not given necessary attention. Using models for analyzing and forecasting economic processes caused by the practical need to adopt better and effective management decisions. One of the main tasks of the models should be to forecasting the indicators and processes of socio-economic development, as well as to identify causal relationships between factors and their potential impact on the final results of socio-economic activity. The article justifications the need for economic and mathematical modeling to assess performance and forecasting social and economic development to improve the quality and efficiency of decision-making. It is applied aspects of usage the method of statistical equations of dependencies as an effective auxiliary tool for decision making in the process of policy-making of financial and budgetary and social areas of the state are presented. The basic problems that allow to solve the method of statistical equations of dependencies are considered. In particular, identifying relationships and determining correlations between individual economic parameters, determining the measure of influence of factors on the performance indicator, as well as their prediction on the basis of predetermined (defined) parameters. An important aspect is also the ability to determine the optimal (or target) values of the factors and performance indicators of socio-economic development, identify relationships, patterns and trends. The proposed approaches make it possible to use the method of statistical equations of dependencies to analyze and predict socio-economic development indicators.